AN UPDATE ON RESOURCES, PROCEDURES AND HEALTHCARE PROVISION IN PAIN UNITS: A SURVEY OF SPANISH PRACTITIONERS - Polo-Santos, Mar; Videla-Cés, Sebastián; Pérez-Hernández, Concha; Mayoral-Rojals, Víctor; Ribera-Canudas, Mª Victoria; Sarría-Santamera, Antonio (International Journal of Environmental Research and Public Health, 2021)
Multidisciplinary pain treatment units are recommended to provide comprehensive diagnosis and treatment of chronic pain, a complex clinical syndrome and one of the leading causes of disability worldwide. The objective of this study was to provide updated results on the situation of pain treatment units in Spain and to determine compliance with recommendations proposed by de Spanish Ministry of Health (SMH). A cross-sectional, prospective, multicenter survey was performed, collecting data on resources, procedures and healthcare provision. Between March and May 2019, the Spanish Pain Society sent an invitation letter to 183 pain units with a link to the questionnaire. Sixty-nine units from 13 regions agreed to participate....
Keywords: pain unit; assessment; questionnaire; multidisciplinary care